FORMULATION AND EVALUATION OF TASTE MASKED ORAL SUSPENSION OF CEFUROXIME AXETIL USING HYDROXYPROPYL-BETA-CYCLODEXTRIN - Prabhakaran, Renju; K, Janakiraman; Harindran, Jyoti (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Cefuroxime axetil is a prodrug of Cefuroxime, which is extremely bitter in taste, which reduces the patient compliance when taken as oral suspension especially in pediatric population. The objective of this study was to mask the bitter taste of Cefuroxime axetil using Hydroxy propyl betacyclodextrin [HP- Betacyclodextrin] by inclusion complexation method. Methods: The complexation of Cefuroxime axetil and HP- Betacyclodextrin was carried out at 1:1, 1:2, 1:2.5 and 1:3 ratios respectively. The prepared suspension was evaluated for various parameters like pH, viscosity, redispersibility, pourability, assay and invitro dissolution profile. A comparative evaluation of the taste masking was carried out for the developed formulations and marketed product. Results: All the formulations and the marketed product were meeting all the quality parameters. Formulations with 1:3 and 1:2.5 ratios showed better taste masking compared to the marketed product and the formulation with 1:2.5 ratio shown to have better invitro dissolution pattern. Conclusion: Considering the invitro dissolution profile and taste evaluation with marketed product, formulation with 1:2.5 ratio of Cefuroxime axetil and HP- Betacyclodextrin was selected as the optimum formulation. Keywords: Cefuroxime axetil, Taste masking, Betacyclodextrin, Inclusion complexation.